The economic effects of real estate investors - Garriga, Carlos; Tsouderou, Athena; Gete, Pedro (John Wiley and Sons Inc, 2023)
We show five new results about small- and medium-sized real estate investors (SMREI) who participate through legal entities in US housing markets. First,SMREI have the largest growth across all cities post Great Recession,in contrast to Wall Street Landlords who concentrate in superstar cities. Second,SMREI increase house price growth and price-to-income ratio,especially in the bottom price tier. Third,this effect is reversed as investors trigger a medium-run supply response. Fourth,in areas with a high supply elasticity,SMREI affect rents more than prices. Finally,SMREI change the composition of the housing stock in favor of multifamily units. © 2023 American Real Estate and Urban Economics Association.
Keywords: 54 Geografía::5403 Geografía humana; ODS 11 - Ciudades y comunidades sostenibles